ADVERBIAL CLAUSES FOUND IN “LEAGUE OF LEGENDS” WEBSITE - Nyoman Ryan Ega Jayendra; I Nyoman Kardana; I Gusti Ngurah Adi Rajistha (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
The use of adverbial is immensely complex. Adverbials can be filled by many different word classes and come in many different forms; the most compared to other sentence elements. Moreover, adverbials can also convey a huge number of meanings. Hence, with this great complexity, research of adverbials needs to carry out, with analysing the forms and the meanings of adverbial clause as the aims of this research. The data source of this research comes from the official website of a video game “League of Legends”. The data collection was done in several actions; opening the data source, reading (the characters’ story), note-taking, and identifying the sentences that consist of adverbial clauses. Furthermore, the collected data were analysed descriptively by using Quirk’s theory of adverbials. The result of the research showed that three forms of adverbial clauses and seven meanings of adverbial clauses were found in “League of Legends” Website. The three forms of adverbial clauses found were finite clauses, non-finite clauses, and verbless clauses. The seven meanings of adverbial clauses found were clauses of time, clauses of place, clauses of condition, clauses of concession, clauses of reason or cause, clauses of purpose, and clauses of result.